An Analytical Study of Sirah Discussions in Tafsir Zad al-Masir: An Exploration of Methodologies: تفسیر زادالمسیر میں مباحث سیرت کے اسالیب کا تجزیاتی مطالعہ - Saqib, Muhammad; Hussain, Dr. Sajjad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This research undertakes a comprehensive analysis of the methodologies employed in discussing Sirah (Prophetic biography) within Tafsir Zad al-Masir, a renowned Quranic exegesis. The study examines the approaches, techniques, and styles utilized by the commentator (Imam Ibn e Jozi) to integrate Sirah narratives into the broader framework of Quranic interpretation. Key aspects of the analysis include: Contextualization of Sirah within Quranic verses Use of Hadith and other historical sources Biographical and historical contextualization Thematic and theological connections Linguistic and literary devices This research aims to contribute to a deeper understanding of the intersections between Quranic exegesis and Sirah studies, shedding light on the commentator’s hermeneutical approaches and the significance of Sirah in Islamic scholarship.